Study on Interaction of Cationic Porphyrazine with Synthetic Polynucleotides - Hamid Dezhampanah; Soghra Fyzolahjani (Analytical Cellular Pathology)
Interactions of cationic tetrakis (N, N′, N″, N‴- tetramethyltetra-3, 4-pyridinoporphyrazinatozinc (II) (Zn (tmtppa)) with synthetic polynucleotides, poly (G-C) and poly (A-T), and calf thymus DNA have been characterized in 7.5 mM phosphate buffer of pH 7.2 by UV-Vis absorption and fluorescence spectroscopy. The appearance of hypochromicity more than 30% in UV-Vis spectra of porphyrazine due to interaction of both poly (G-C) and poly (A-T) indicates interaction similar to that of porphyrazine with DNA.